IMPLEMENTASI METODE TAJRIBI, BURHANI, BAYANI, DAN IRFANI DALAM STUDI FILSAFAT PENDIDIKAN ISLAM - Fatima Rahma Rangkuti (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Abstract: The tajribi method (observation and experiment) is applied by scientists in studying physical and material objects, as has been done by Ibn Haitsam in the theory of vision. The burhani (logical) method is applied by philosophers to understand non-physical and spiritual objects, in the Qur'an the burhan method is implied by the words afala tatafakkarun, afala ta'qilun, afala tubshirun, afala tanzhurun, and afala yatadabbaru. The method of bayani (tafsir / takwil) is used by the mufassir to explore knowledge in religious books: Qur'an and hadith, by the bayani method the verses of the Qur'an are classified into several categories, such as the verses of muhkamat and verses mutasyabihat (ambigius) and so on. And the irfani method (intuitive) is used by Sufis to witness non-physical and spiritual objects directly by means of exercises such as dhikr, tasbih and so on. The methods of tajribi, burhani, bayani, irfani and tajribi, these four methods actually have their respective domains in the world of education, but in this reality, there is an imbalance between these four methods, even though the integration between the four methods will certainly produce knowledge very complete. Key word: Implementation of tajribi, burhani, bayani and irfani methods in islamic education philosophy study